Second-Term Blues : How George W. Bush Has Governed - Ornstein, Norman J.; Fortier, John C. (Book collections on Project MUSE., 2007)
"Illuminates the priorities, governing tendencies, and leadership style of a president in his second term. Reveals how Bush's foreign policy defines and restricts his presidency, dissects America's changing political mood and considers how the president's personal style fits into that milieu, and defines his executive style"--Provided by publisher.